Myopia Management in Daily Routine – A Survey of European Pediatric Ophthalmologists - Eppenberger, Leila Sara; Sturm, Veit (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose Assessment of diagnostic and therapeutic strategies currently used in routine practice for myopia management in Europe.Methods Online survey study including 11 main questions. The questionnaire was sent to members of the European Paediatric Ophthalmology Society (EPOS). The following items and questions were surveyed: I. Profession and workplace of the survey participants. II. Preventive measures and recommendations for myopia management, a) regarding reading distance and near work, b) optical tools, i.e., application of Defocus Incorporated Multiple Segments (DIMS) glasses, near additions, or contact lenses, and c) the application of atropine eye drops. III. Application of additional diagnostic tools.Results Forty-eight individuals completed the survey. Of the respondents, 88% (n = 42) affirmed that they generally gave advice on strategies for myopia prevention and management strategies. Almost all study participants (n = 41; 85%) recommend outdoor time as a preventive measure. The recommendation on near distance is given less frequently, with 28 (58%) participants confirming that they do recommend a “safe” reading distance, and 15 (31%) negating this. Eight (17%) survey participants recommend using near addition glasses, while 36 (75%) do not. Similarly, 35 (73%) respondents do not apply DIMS glasses and 8 (17%) apply them. Fourteen (29%) participants recommend myopia-reducing contact lenses while 30 (63%) do not, and 29 (60%) confirmed that they applied atropine eye drops to slow myopia progression while 14 (29%) do not prescribe these eye drops. The majority of respondents (n = 25; 86%) who prescribe atropine eye drops use atropine 0.01% eye drops.Conclusions Prevention and therapeutic management of childhood myopia is an essential part in the daily routine of pediatric ophthalmologists. Substantial agreement was found for the protective role of outdoor time (85%). The only common therapeutic approach is the administration of atropine eye drops (60%).
Keywords: myopia management; Europe; prevention; optical interventions; atropine